2018
DOI: 10.2147/ott.s163076
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of the number of lymph nodes examined in different stages of colorectal mucinous adenocarcinoma

Abstract: BackgroundMucinous adenocarcinoma (MC) is a special kind of colorectal adenocarcinoma that occurs more frequently in young patients and females, but the prognostic effect of lymph nodes in MC patients is unclear. This population-based study was conducted to analyze the prognostic value of the number of lymph nodes examined in different stages of colorectal MC.MethodsWe included 17,001 MC patients from the Surveillance, Epidemiology, and End Results program database between 2003 and 2013, of which 12,812 (75%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…The number of LNs examined and LN ratios are two variables frequently used to assess the impact of lymph node metastasis on postoperative survival in colon cancer 2022,27–29 . It was suggested that at least 12 LNs should be examined pathologically to determine the absence of lymph node metastasis in colon cancer patients 1719 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of LNs examined and LN ratios are two variables frequently used to assess the impact of lymph node metastasis on postoperative survival in colon cancer 2022,27–29 . It was suggested that at least 12 LNs should be examined pathologically to determine the absence of lymph node metastasis in colon cancer patients 1719 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevant debate has never ended because optimal other than 12 have been implied, such as 20 23 , 21 24 , and 22 25 . Similar to tumor sidedness, the prognostic value of the number of LNs examined varied depending on stages of colon cancer 21,22,26 . In addition, the prognostic effect of LN ratio, defined as the ratio of the number of positive LNs to the total number of LNs examined, has been demonstrated in stage II and III colon cancer patients 27,28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonoscopy is the best investigation to detect the early neoplastic changes and even if a polyp is seen on colonoscopy it is removed at the same time [26,27]. Unfortunately in Pakistan screening is not done as a routine investigation, particularly in rural areas because of illiteracy and lack of access to health care centre and even in urban areas due to lack of awareness patients reach the health care centres in late stages [28][29][30][31][32][33][34][35][36][37][38][39]. Even when patient go to a hospital with symptoms of bowel disease colonoscopy is not done as a screening test.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that higher age (> 65 years), tumor grades including moderately, poorly, and undifferentiated tumors, tumor location in the rectum, preoperative CEA level (> 5 ng/mL), higher pathological T or N stage, intestinal obstruction, and perineural infiltration were all significantly associated with poor OS in MAC[ 7 , 120 ]. A greater number of lymph nodes examined (no fewer than 12) significantly increased OS (HR = 0.601, 95%CI: 0.537-0.673, P < 0.001) and CSS (HR = 0.582, 95%CI: 0.511 to -0.664, P < 0.001) in patients with colorectal MAC[ 120 ]. BRAF mutations were significantly associated with CRC-specific mortality (multivariate HR = 1.64, 95%CI: 1.18-2.27, P = 0.003), while MSI-H was associated with a statistically significant reduction in CRC-specific mortality (multivariate HR = 0.28, 95%CI: 0.17-0.46, P < 0.001).…”
Section: Prognosismentioning
confidence: 99%